Kesehatan Gigi Anak Autis - Anggraini, Laelia Dwi (Universitas Muhammadiyah Yogyakarta, 2007)
Autism is a development disturbance in children, which includes communication, interaction and behavior. Autistic children suffer more serious mouth disease because disability to brush their teeth. The main problem in handling autistic children is building a good communication and giving attention in health teeth. Good cooperation from parents, autistic child, and their dentist is a key success for the teeth care of autistic children. This paper explains about autism including its etiology, diagnosis, therapy and how to handle the mouth and teeth health of autistic children.Autis adalah gangguan perkembangan pada anak yang meliputi komunikasi, interaksi dan kebiasaan. Anak autis mempunyai gangguan kesehatan mulut yang serius, disebabkan ketidakmampuannya menyikat gigi. Masalah utama menangani anak autis adalah membangun komunikasi dan memberi perhatian pada kesehatan giginya. Kerjasama yang baik antara orang tua, anak autis dan dokter giginya adalah kunci kesuksesan perawatan gigi anak autis. Makalah ini menerangkan tentang autis meliputi etiologi, diagnosis, terapi dan bagaimana menangani kesehatan gigi dan mulut anak autis.